2014
DOI: 10.7863/ultra.33.7.1155
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of Prevalence of the Right Heart

Abstract: The sonographic parameters of coexisting intracardiac anomalies and diagnosis before 24 gestational weeks are significant independent predictors of a poor prognosis in fetuses with prevalence of the right heart. Combinations of these risk factors may be useful in prenatal consultation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…First, FL has been reported to provide the highest correlation coefficient with the most cardiovascular dimensions, and second, ethnic differences are associated with different intrauterine growth rates. [61011] In some previous studies that have quantitatively assessed the RV/LV ratio,[1213] investigators chose an RV/LV ratio of 1.2 as the cutoff for RDH. However, there were studies reported an average upper limit of the RV/LV ratio of other different data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, FL has been reported to provide the highest correlation coefficient with the most cardiovascular dimensions, and second, ethnic differences are associated with different intrauterine growth rates. [61011] In some previous studies that have quantitatively assessed the RV/LV ratio,[1213] investigators chose an RV/LV ratio of 1.2 as the cutoff for RDH. However, there were studies reported an average upper limit of the RV/LV ratio of other different data.…”
Section: Discussionmentioning
confidence: 99%
“…These same proportions were reported by Peng et al . [12] and Jung et al . [18] Moreover, the RV width Z -score and RV/LV ratio in the third-trimester group were significantly different from those in the second-trimester group.…”
Section: Discussionmentioning
confidence: 99%